2016
DOI: 10.1111/jhn.12407
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between dietary intake and academic achievement: a systematic review

Abstract: This review highlights that moderate associations exist for dietary intakes characterised by regular breakfast consumption, lower intakes of energy-dense, nutrient-poor foods and overall diet quality with respect to outcomes of academic achievement. Future studies should consider the use of validated dietary assessment methods and standardised reporting of academic achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
129
4
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 47 publications
6
129
4
16
Order By: Relevance
“…Current diets are characterised by inadequate intakes of foods such as vegetables and whole grains, in combination with excess intakes of nutrient-poor food and drinks [1,2]. Poor diet quality is inversely associated with risk factors for chronic disease such as excess weight gain [3] as well as poorer child development outcomes [4,5]. Influencing the settings where children live, learn and play is needed to improve the quality of what children eat and drink to support optimal growth, health and development [6].…”
Section: Introductionmentioning
confidence: 99%
“…Current diets are characterised by inadequate intakes of foods such as vegetables and whole grains, in combination with excess intakes of nutrient-poor food and drinks [1,2]. Poor diet quality is inversely associated with risk factors for chronic disease such as excess weight gain [3] as well as poorer child development outcomes [4,5]. Influencing the settings where children live, learn and play is needed to improve the quality of what children eat and drink to support optimal growth, health and development [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the quality of these studies was considered low, in particular with regard to the poor use of validated tools for accurately measuring dietary intake and a lack of appropriate adjustments for potential confounding factors in the analyses. Accurate assessment of dietary intake is essential to substantiate the link with academic achievement (7,8) ; for example, using validated dietary assessment tools and, ideally, a broad or holistic assessment of diet that goes beyond individual food groups or meal patterns. Furthermore, key factors that are known to influence diet or academic achievement need to be accounted for to more accurately assess this relationship, such as socio-economic status and gender (9,10) .…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have approached the effects of short-term exposure to a WD on academic outcomes [19], very few have focused on foods consumed during snack times. We found that unhealthy snacking was correlated with lower high school GPA and rate of graduation, as well as a reduced likelihood of taking college admission exams.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of interventions that emphasize the relationship between diet type and cognition and academics have been designed for infants and young children [6,19,52], who are less independent in their food choices. For health promotion purposes, unhealthy dietary habits during adolescence are usually said to be related to early onset of cardiometabolic disorders, including high blood pressure, type-2 diabetes and coronary heart disease, while arguments based on the potential cognitive impact of diet are still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation